INFLUENCE OF RISK MANAGEMENT AND MACRO ECONOMY ON THE PERFORMANCE OF ISLAMIC BANK IN INDONESIA - Hesniati Hesniati; Soecipto Soecipto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Islamic banking has developed rapidly in recent years, especially in Indonesia, so it is necessary to conduct research to examine the effect of risk management and macroeconomics on the performance of Islamic banking in Indonesia. Data analysis used the panel regression method with 14 Islamic commercial bank companies starting from 2016 to 2020. The results showed that the financing to deposit ratio had an effect on the performance of Islamic banks, while net-performing financing and the cost to income ratio had a negative effect on performance. Islamic Bank. Even so, the interest rate and inflation variables have no significant effect on the performance of Islamic banks.